Toward high-throughput oligomer detection and classification for early-stage aggregation of amyloidogenic protein - Tahirbegi, Bogachan; Magness, Alastair J.; Piersimoni, Maria Elena; Teng, Xiangyu; Hooper, James; Guo, Yuan; Knöpfel, Thomas; Willison, Keith R.; Klug, David R.; Ying, Liming (Frontiers in Chemistry, 2022)
The aggregation kinetics of proteins and peptides have been studied extensively due to their significance in many human diseases, including neurodegenerative disorders, and the roles they play in some key physiological processes. However, most of these studies have been performed as bulk measurements using Thioflavin T or other fluorescence turn-on reagents as indicators of fibrillization. Such techniques are highly successful in making inferences about the nucleation and growth mechanism of fibrils yet cannot directly measure assembly reactions at low protein concentrations which is the case for amyloid-β (Aβ) peptide under physiological conditions. In particular, the evolution from monomer to low order oligomer in the early stages of aggregation cannot be detected. Single molecule methods allow directly access to such fundamental information. We developed a high throughput protocol for single molecule photobleaching experiments using an automated fluorescence microscope. Stepwise photobleaching analysis of the time profiles of individual foci allowed us to determine the stoichiometry of the protein oligomers and probe protein aggregation kinetics. Furthermore, we investigated the potential application of supervised machine learning with support vector machines (SVMs) as well as multilayer perceptron (MLP) artificial neural networks to classify bleaching traces into stoichiometric categories based on an ensemble of measurable quantities derivable from individual traces. Both SVM and MLP models achieved comparable accuracy of more than 80% against simulated traces up to 19-mer, although MLP offered considerable speed advantages thus making it suitable for application to high throughput experimental data. We used our high throughput method to study the aggregation of Aβ in the presence of-metal ions and the aggregation of α-synuclein in the presence of gold nanoparticles.